Sanabilidade de vícios na admissibilidade dos embargos de divergência nos Tribunais Superiores - Tesolin, Fabiano da Rosa (2019)
The present research work aims to demonstrate the relationship between the system of sanity of formal admissibility defects and the importance of the embargos of divergence, based on the fundamental norms contained in the Code of Civil Procedure (Law 13.105/2015). The understanding of divergence liens, as an instrument of uniformity of internal divergence in the jurisprudence of the High Courts and as a means of achieving the system of judicial precedents foreseen in CPC/2015, is also approached with the necessary depth. Afterwards, the significant alteration suggested by the newprocedural ordering in the assumptions of discharges of divergence and the impact of the revocations imposed by Law 13.256/2016 will be analyzed. Next, the procedure of the uniform appeal contained in the internal rules of the Superior Courts and the effects of the embargos of divergence will be faced. The survey further examines the specific admissibility requirements of divergence liens. Finally, it will be studied the system of sanity of formal defects proposed by CPC/2015, its limits and elements, as well as the specific incidence of regularization in the scope of the embargos of divergence